Dampak Penerapan Kecerdasan Buatan (AI) Untuk Manajemen Kurikulum Pendidikan Tinggi Di Jawa Tengah - Jaelani Jaelani; Erwan Hidayat; Febryantahanuji Febryantahanuji (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Key Problem: the development of artificial intelligence technology has increased in the last five years, but testing of the impact of its application to curricula in higher education has been poorly considered and very limited. Objective: to know the interrelationship between the impact of the application of artificial intelligence in contributing to improving student academic achievement. Originality: testing the effectiveness and linkage of the impact of artificial intelligence on the curriculum in higher education with increased student achievement is still very limited. Method: quantitative design with secondary data taken from literature and previous research as many as 50 examples of cases in universities with Koesioner Method. Result: there is an influence of the impact of the application of artificial intelligence on curriculum development in universities. The impact value brought by artificial intelligence is 0.7 which is classified as the Good category. There was a low association of 0.05 between the application of artificial intelligence in the curriculum at 50 universities and the increase in student academic achievement. Novelty: not always the application of artificial intelligence has a bad impact as long as it is balanced with wise use. Suggestion: it is expected that future research will use a wider scope and methods to deepen understanding related to the application of artificial intelligence in the development of higher education systems.